The Temporal Structure of the Running Cycle, an Essential Element in the Analysis: A Critical Review - Felipe Inostroza-Ríos; Pablo Merino-Muñoz; Celso Sánchez-Ramírez; Alejandro Bustamante Garrido; Jorge Pérez-Contreras; Jorge Cancino-Jimenez; David Arriagada-Tarifeño; Esteban Aedo-Muñoz; Ciro José Brito (Biomechanics, 2025)
The running cycle is distinguished from the gait cycle by the presence of a flight phase and distinct biomechanical characteristics. Despite existing frameworks for the temporal segmentation of running, these models remain underutilized in comprehensive biomechanical analyses, particularly for delineating phases, subphases, and key events. This study aims to provide a review of historical and contemporary temporal models of the running cycle and to introduce a unified structure designed to enhance analytical precision. The proposed framework divides the running cycle into two primary phases: (a) contact (subdivided into braking and propulsion subphases) and (b) flight, together with three critical events: (1) initial contact, (2) transition of braking–propulsion, (3) toe-off. While leg swing is not considered a phase in this framework due to temporal overlap with other phases, its recognized importance in running mechanics warrants its integrated analysis under the proposed temporal phase delineation. Additionally, methodologies for identifying these events through dynamometry and motion capture are evaluated, emphasizing their role in contextualizing kinetic and kinematic data. By integrating this temporal structure, the study aims to standardize biomechanical assessments of running technique, fostering more consistent comparisons across studies. Such integration has the potential to not only refine interpretations of running mechanics but also to enable practical advancements in athletic training, injury mitigation, and performance optimization.